Impact of climacteric and depressive symptoms on the quality of life of postmenopausal women - Pawlak, Iwona Ewa; Wolińska, Weronika; Mroczek, Bożena (Family Medicine & Primary Care Review, 2016)
Background. Quality of life consists of many elements that affect the creation of the level of QoL. Women with postmenopausal may experience a phenomenon of loneliness. This phenomenon can be caused by the effects they had on menopausal symptoms and depression from private and professional life. Objectives. The aim of the study was to determine the effect of menopausal symptoms and depression on quality of life in postmenopausal women. Material and methods . The survey was performed among 128 women after menopause. The mean age was 64.20 ± 8.61, median 65 years. The study used a questionnaire consisting of the SF-36, Kupperman Index, Beck Depression Scale and the author’s questionnaire. Results . The sense of mental health – MH women found at most, which was equal to 69.47. Meanwhile, the general level of health – HP was rated the lowest of only 46.68. Of the 128 respondents revealed menopausal symptoms at 32.81% (n = 42) of surveyed women. It has been shown statistically significant relationship between the index of climacteric, and the assessment of QoL in the SF-36 domains: RL M (emotional role functioning) – (χ 2 = 24.33; p = 0.003), MH (mental health) – (χ 2 = 27.27; p = 0.001), EV (vitality) – (χ 2 = 24.28; p = 0.003), P (pain) – (χ 2 = 25.89; p = 0.002), and the Beck Depression Inventory, and the assessment of QoL by SF-36. Conclusions . Menopausal symptoms, the presence of depression and age have a significant impact on the quality of life of women in postmenopausal period.